A new lattice Boltzmann method for melting processes of high Prandtl number phase change materials. (September 2021) - Du, Wenhui; Chen, Sheng; Wu, Guoqiang
Abstract: The lattice Boltzmann method has shown its advantages to model melting processes in thermal energy storage systems. However, the organic phase change materials which are popularly used in modern thermal energy storage systems and featured by a large Prandtl number, have raised a big challenge for the simulation by the lattice Boltzmann method, as a large Prandtl number will cause a large discrepancy between the relaxation times for flow and temperature fields in the lattice Boltzmann method. And such discrepancy will cause serious numerical instability. In this work, a new lattice Boltzmann model is proposed to address this challenge. Three benchmark test cases are adopted to validate the capability of the present lattice Boltzmann model for simulating melting processes of organic phase change materials with large Prandtl numbers ( P r up to 56.2). The present numerical results are in good agreement with the existing data obtained numerically and experimentally. Compared with the available lattice Boltzmann approaches, the present model can capture the melting interface accurately with much less grid density. Highlights: A novel lattice Boltzmann method for melting processes is designed. It can simulate organic phase change mate. Its computational efficiency is higher.